Preaching when life depends on it: climate crisis and Gospel hope - Bullitt-Jonas, Margaret (Anglican theological review, 2021)
Many preachers avoid delivering sermons about the climate crisis. Bullitt-Jonas reflects on the power of sermons to awaken moral courage, arguing that strong sermons on climate change create the conditions for spiritual awakening and prophetic action. She considers six ideas for preachers, starting with how to frame the climate emergency in terms of Christian theology. She reflects on how to approach the lectionary; how to be adequately informed about climate science; how to connect climate change with other issues, such as coronavirus and racial and economic justice; why and how to infuse sermons with the empowering love of God; and individual and collective actions to encourage. Preachers play an essential role in helping Christians understand the climate crisis as a religious and moral issue and in creating a social "tipping point" that propels rapid change. The article includes resources for "best practices" in climate preaching and communication.